2014
DOI: 10.1210/en.2013-1755
|View full text |Cite
|
Sign up to set email alerts
|

Role of Androgens in Sex Differences in Cardiac Damage During Myocardial Infarction

Abstract: Age-specific incidence of ischemic heart disease in men is higher than in women, although women die more frequently without previous symptoms; the molecular mechanism(s) are poorly understood. Most studies focus on protection by estrogen, with less attention on androgen receptor-mediated androgen actions. Our aim was to determine the role of androgens in the sex differences in cardiac damage during myocardial infarction. Mature age-matched male and female Sprague Dawley rats, intact or surgically gonadectomize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 44 publications
2
18
0
Order By: Relevance
“…Differential regulation of these receptors may differ between males and females and whether there is cross-reactivity should also be considered. In recent studies, we did not find any differences in protein levels of AR, ER-a and ER-b, between male and female rats [58], in agreement with previous reports [70,75]. In contrast, sex differences in MR mRNA levels have been reported in rat brain, while treatment with estrogen decreased MR mRNA expression and binding in the hippocampus [66].…”
Section: Regulation Of Expression Levels Of Receptors In the Heartsupporting
confidence: 93%
See 4 more Smart Citations
“…Differential regulation of these receptors may differ between males and females and whether there is cross-reactivity should also be considered. In recent studies, we did not find any differences in protein levels of AR, ER-a and ER-b, between male and female rats [58], in agreement with previous reports [70,75]. In contrast, sex differences in MR mRNA levels have been reported in rat brain, while treatment with estrogen decreased MR mRNA expression and binding in the hippocampus [66].…”
Section: Regulation Of Expression Levels Of Receptors In the Heartsupporting
confidence: 93%
“…We have recently identified key roles for sex steroids during MI, to regulate the balance between autophagy and apoptosis ( Fig. 1), with less cardiac damage in females due to reduced apoptosis and sustained autophagy [58]. These experimental studies are confirmed clinically, with higher apoptotic rate in the peri-infarct region of post-mortem hearts from men dying after acute MI than women [59].…”
Section: Sex Hormones and Cardiac Actions Of Aldosteronementioning
confidence: 66%
See 3 more Smart Citations